KARAKTERISTIK SIFAT FISIKO-KIMIA PATI KELAPA SAWIT - Ridwansyah, M. Zein Nasution, Titi C. Sunarti dan Anas M. Fauzi (Department of Agroindustrial Technology, Bogor Agricultural University, 2007)
ABSTRACTThe oil palm trunks become a waste from the rejuvenation of the oil palm plantation. The extraction of the oil palm trunk can produce about 4.7% of starch. The starch extracted was characterized for its physical and chemical properties and compared to the commercial starch of sago and tapioca. The starch of oil palm contains fat (0.37%), ash (0.68%), fiber (1.78%) which were higher than those of sago and tapioca. However, the amylose content (28.76%) of the oil palm starch was lower. The gelatinization temperature of oil palm starch (77oC) was similar with that of sago, but it was higher than that of tapioca. The whitish degree (83.02%) and the paste clearance (15.4% T) of the oil palm’s starch were lower than sago’s and tapioca’s. Based on the amylograph analysis, the oil palm starch was categorized normal and had final viscosity which was higher than commercial starch. It was indicated that oil palm starch was easily to be retrograded and suggested to be used as an adhesive material.Key words: oil palm trunk starch, physico-chemical properties